Recent advances of biomimetic nano-systems in the diagnosis and treatment of tumor - Anning Li; Jiawei Zhao; Jingru Fu; Jia Cai; Peng Zhang (Elsevier, 2021)
The lack of effective methods of diagnosis and treatment presents a major barrier to combat against tumor. The biomimetic concept is an emerging field that expresses great application potential in tumor fighting. Strategy for combining nano-systems with biomimetic technology has gained increasing attention that is proved bioinspired, environmentally benign, and promising. Herein, we provide an up-to-date review of biomimetic nano-systems as well as their applications in tumor therapy. In addition, the challenges and future directions of biomimetic nano-systems to achieve clinical translation are also pointed out.